PENGEMBANGAN BAHAN AJAR BAHASA ARAB BERBASIS PENDIDIKAN KARAKTER DI MADRASAH IBTIDA’IYAH MI’ROJUL IHTIDA BONDOWOSO: Pengembangan Bahan Ajar Bahasa Arab Berbasis Pendidikan Karakter untuk Sekolah Dasar Islam - Firda Aulia Denisa; Sutaman; Mamluatu Solihah (ELOQUENCE : Journal of Foreign Language, 2026)
Background: Teaching materials play an important role in the learning process because they serve as a primary reference for teachers and students in achieving learning objectives. When teaching materials are inappropriate, irrelevant, or not aligned with students’ needs, they may affect not only learning outcomes but also students’ character development. Therefore, teaching materials are needed that not only teach language skills but also help shape students’ attitudes and moral values. Purpose: This study aims to develop Arabic teaching materials based on character education at Islamic Elementary School Mi’rojul Ihtida Bondowoso. Method: This study employed a Research and Development (R&D) method using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. Results and Discussion: The results show that the developed teaching materials obtained a feasibility score of 82.5% from the material expert (categorized as feasible) and 97.5% from the design expert (categorized as highly feasible). The average student pre-test score increased from 59.4 to 83.2 in the post-test. The paired sample t-test results indicate a significant difference between students’ learning outcomes before and after the use of the teaching materials. The N-gain value of 0.5893 (58.93%) falls into the moderate category. Conclusion and Implications: The development of character education–based Arabic teaching materials is considered valid and effective for use in the learning process at Islamic Elementary School Mi’rojul Ihtida Bondowoso. These teaching materials contribute to integrating Arabic language learning with the development of character values among elementary-level students.